MASLAHAH CONCEPT ANALYSISTOWARDS 2016 TAX AMNESTY POLICY IN INDONESIA - Ade Tachrizatu Wirda, Faridl Noor Hilal, M.M.A (Universitas Darussalam Gontor, 2018)
Indonesia is projected to meet the potential globalrisk. Where actually it has a significant implication onIndonesian’s economic rate in the future. In the otherhand, the expenditure of nation is increasing year by year.But,there is a gap between the tax compliance and the thetax potential. So, the Indonesian government has a tre-mendous errand min its program is establishing a crediblefiscal policy. Towards its fiscal policy, the government triesto increase the nation revenue trough Tax Amnessty policy.However, the tax amnesty conducted the result of increasingof tax compliance and tax revenue in the future. Hence, thispolicy has a controversial issue. The paper is a qualitativeresearch which try to describe more deeper the meaning ofMaslahah. This paper tries to analyze more the Maslahahconcept towards Tax Amnesty policy in the term of Lawof Islamic Economic. In this paper, the researcher observethe literal meaning of Maslahah and trying to describethe interest and benefits of Tax Amnesty in its sort andlong term. Therefore, the benefits may lead to the publicwelfare. But, the result of the research found that there aresome lacks of Indonesia Tax Amnesty policy in its absenceof tracking source, as its one of incentives. So, it causes toopposite of the Islamic Law to Al-Qur’an, which shouldkeep the own of wealth well. Furthermore, the existence oftax amnesty policy should be more considered due to thisissue, affecting in its level of importance towards Maslahahand Shari’ah compliance is one step down. Overall, theincentives of tax amnesty should be discussed carefully on its further implication –where the tax amnesty presents ahigh risk issue for the nation development.